Study on seismic performance of SRC leaning beam-column exterior joints in the main workshop of CAP1400 nuclear power plant. (December 2021) - Xu, Zhen-Hua; Bai, Guo-Liang; Zhao, Jin-Quan; Liu, Biao
Abstract: This paper focuses on the seismic performance of steel reinforced concrete (SRC) leaning beam-column exterior joints in the main workshop of a large capacity nuclear power plant. Quasi-static tests of three specimens with different inclination angles in 1/4 scale of prototype model were carried out. The specimen' mechanical characteristics, failure modes, hysteresis performance, and energy dissipation capacity were investigated. Based on the quasi-static tests of SRC leaning beam-column exterior joints, the nonlinear test process was simulated and analyzed using ABAQUS software. Besides, the inclination angle of the leaning beam, yield strength of shaped steel, volume-stirrup ratio, and steel content on seismic performance of joints were analyzed by the validated finite element model (FEM). The joint's carrying capacity and deformation performance can match the seismic design requirements when the inclination angle of the leaning beam was less than 10°. Furthermore, the increase of steel content can enhance the carrying capacity and deformation performance in joints. When the steel content of column and leaning beam was 5.83% and 5.78%, respectively, the ultimate bearing capacity of the joint was increased by about 31% compared with steel content ρ c  = 2.98% and ρ b  = 2.97%.